2009
DOI: 10.1590/s1516-35982009001300032
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias na suplementação de vacas leiteiras no semi-árido do Brasil

Abstract: A região semi-árida do Brasil prolonga-se por uma área de 928 km² abrangendo uma parte do norte dos estados de Minas Gerais e Espírito Santo, os sertões da Bahia, Sergipe, Alagoas, Pernambuco, Paraíba, Rio Grande do Norte, Ceará e Piauí e mais 45 municípios do sudeste do Maranhão. A população é predominantemente rural e a ocupação principal de sua força de trabalho é a agropecuária. A pecuária leiteira aparece como uma das poucas opções nas regiões semi-áridas, principalmente no nordeste do Brasil, onde a alim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 7 publications
1
22
0
19
Order By: Relevance
“…The high degradability of spineless cactus has become known for maximizing the rumen fermentation capacity and increasing microbial protein synthesis, SCFA production and, consequently, nutrient conduction for animals (Ferreira et al, 2009). It was found that maximum production of total SCFA (57.7 μmol mL -1 , Table 4) was obtained with 63.7% replacement of wheat bran by spineless cactus.…”
Section: Discussionmentioning
confidence: 99%
“…The high degradability of spineless cactus has become known for maximizing the rumen fermentation capacity and increasing microbial protein synthesis, SCFA production and, consequently, nutrient conduction for animals (Ferreira et al, 2009). It was found that maximum production of total SCFA (57.7 μmol mL -1 , Table 4) was obtained with 63.7% replacement of wheat bran by spineless cactus.…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian semiarid region is characterized by high temperatures, high evaporation rate and marked irregularity in rainfall distribution (both in time and space), with long drought periods (FERREIRA et al, 2009). These factors make livestock vulnerable to forage resource seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, during the dry season, the amount of grazable biomass is dramatically reduced and the flocks are affected by forage scarcity (Santos, Lira et al, 2010;Pereira Filho, Silva, & Cézar, 2013). Some alternatives have been suggested to minimize the impact of variation in forage allowance on flocks, namely, forage conservation and use of forage adapted to semi-arid areas (Ferreira, Silva, Bispo, & Azevedo, 2009). The spineless cactus occupies a prominent position due to its productivity, nutritional value and distribution in the Brazilian semi-arid.…”
Section: Introductionmentioning
confidence: 99%